Guidance Document on Scientific criteria for grouping chemicals into assessment groups for human risk assessment of combined exposure to multiple chemicals. (17th December 2021) - ,; More, Simon John; Bampidis, Vasileios; Benford, Diane; Bragard, Claude; Hernandez‐Jerez, Antonio; Bennekou, Susanne Hougaard; Halldorsson, Thorhallur Ingi; Koutsoumanis, Konstantinos Panagiotis; Lambré, Claude; Machera, Kyriaki; Naegeli, Hanspeter; et al.
Abstract: This guidance document provides harmonised and flexible methodologies to apply scientific criteria and prioritisation methods for grouping chemicals into assessment groups for human risk assessment of combined exposure to multiple chemicals. In the context of EFSA's risk assessments, the problem formulation step defines the chemicals to be assessed in the terms of reference usually through regulatory criteria often set by risk managers based on legislative requirements. Scientific criteria such as hazard‐driven criteria can be used to group these chemicals into assessment groups. In this guidance document, a framework is proposed to apply hazard‐driven criteria for grouping of chemicals into assessment groups using mechanistic information on toxicity as the gold standard where available (i.e. common mode of action or adverse outcome pathway) through a structured weight of evidence approach. However, when such mechanistic data are not available, grouping may be performed using a common adverse outcome. Toxicokinetic data can also be useful for grouping, particularly when metabolism information is available for a class of compounds and common toxicologically relevant metabolites are shared. In addition, prioritisation methods provide means to identify low‐priority chemicals and reduce the number of chemicals in an assessment group. Prioritisation methods include combined risk‐based approaches, risk‐based approaches for single chemicals and exposure‐driven approaches. Case studies have been provided to illustrate the practical application of hazard‐driven criteria and the use of prioritisation methods for grouping of chemicals in assessment groups. Recommendations for future work are discussed. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2021.EN-7029/full